The intergenerational transmission of mental and physical health in the United Kingdom - Panka Bencsik; Timothy Halliday; Bhaskar Mazumder (Federal Reserve Bank of Chicago, 2021)
We estimate intergenerational health persistence in the United Kingdom using Quality Adjusted Life Years (QALY), a broad measure of health derived from the SF-12 Survey. We estimate that both the rank-rank slope and the intergenerational health association (IHA) are 0.21. We use components of the SF-12 to create mental and physical health indices and find that mental health is at least as persistent across generations as physical health. Importantly, parents' mental health is much more strongly associated with children's health than parents' physical health indicating that mental health might be a more important transmission channel. Finally, we construct an overall measure of welfare that combines income and health, and estimate a rank-rank association of 0.31. This is considerably lower than a comparable estimate of 0.43 for the US, suggesting greater mobility of overall welfare in the UK than the US.
Keywords: J62; I14; 330; intergenerational health mobility; mental health; physical health; United Kingdom